Structure of the essential peptidoglycan amidotransferase MurT/GatD complex from Streptococcus pneumoniae - Cécile Morlot (Nature Portfolio, 2018)
The amidotransferase MurT/GatD complex catalyzes peptidoglycan precursor amidation in some Gram-positive bacteria. Here the authors present the crystal structure of the Streptococcus pneumoniae MurT/GatD complex and provide mechanistic insights, which are of interest for drug development.